Multi-Access RF Frequency Dissemination Based on Round-Trip Three-Wavelength Optical Compensation Technique Over Fiber-Optic Link - Mingyu Jiang; Yaqing Chen; Nan Cheng; Yanguang Sun; Jialiang Wang; Rui Wu; Fei Yang; Haiwen Cai; Youzhen Gui (IEEE Photonics Journal, 2019)
In this paper, we propose a tree-like topology networking scheme based on round-trip three-wavelength optical compensation technique over fiber-optic link. This scheme simplifies the system complexity of the local site, improves the scalability of the frequency dissemination network, and reduces the influence of Rayleigh backscattering on the local and remote sites. The feasibility of the scheme is verified by a set of fiber-optic frequency dissemination network, with a transmission frequency of 1 GHz. The network consists of two remote sites with distances of 20 and 55 km far from the local site, and the frequency compensation system is optimized. The experimental results show that the fractional frequency stability of the 20 and 55 km fiber links can reach 8.6 × 10−15@1s, 7.6 × 10−18@104s, and 1.3 × 10−14@1s, and 8.1 × 10−18@104s. The limitations of electrical amplifiers, WDM, and group velocity dispersion on long-term stability and network capacity are discussed. Our system demonstrates that the stable sharing of frequency signals from ultra-stable frequency sources at any site within a large metropolitan area is achievable.